Supplementing sows with the leucine metabolite beta-hydroxy-beta-methylbutyrate and vitamin D3 improves piglet birth weights that may lead to increased weaning weights - Fuller, John C.; Rathmacher, John A.; Castro, Fabricio Faleiros; Chaves, Rhuan Filipe; Mohr, Mike (Frontiers in Animal Science, 2022)
Previous university studies demonstrated supplementing sows with calcium beta-hydroxy-beta-methylbutyrate (CaHMB) in late gestation and/or lactation improved piglet weights through weaning. Two studies were conducted at commercial farrowing operations to test if the results would translate to commercial operations. Sows in both trials were randomized to receive either 3 g/d CaHMB plus 500 IU/d Vitamin D3 (HMB/D) or a calcium carbonate containing control top-dressed to feed from day 104 of gestation through weaning. Sows were randomly assigned to either HMB/D (n=41 trial 1 and n=26 trial 2) or control (n=46 trial 1 and n=26 trial 2). Data were analyzed using a general linear model with main effects of group, treatment, and group by treatment interaction. Treatment with HMB/D had no effect on sow weights, lactational weight loss, stillborn or mummified piglets. In trial 1, the control group had an increased number of live born piglets, which at 24-hours tended to be greater, and no difference in liveborn or 24-hour piglet numbers were seen in trial 2. In trial 1, HMB/D increased piglet live birth (P < 0.03), and 24-hour weights (1,490±30.1 versus 1,390±28.8 g in HMMB/D and control piglets, respectively, P < 0.02). Farm practices were to equalize piglet numbers across sows by cross-fostering. After cross-fostering, the 24-hour average piglet weights were not different and further advantages to supplementation were not observed (P = 0.21). In trial 2, birth and 24-hour weights of the piglets from HMB/D-supplemented sows were increased (P < 0.0001). Piglets from sows supplemented with HMB/D were 9.7% heavier at birth and 9.2% heavier at 24 hours (1549±22.0 and 1,419±21.2 in HMB/D and control, respectively). A difference was observed in weaning age (P < 0.0001), and weaning weights were adjusted to a 21-day weights (5426±103.5 and 5,205±99.5 for HMB/D and control piglets, respectively, P = 0.12). Analysis by group showed HMB/D tended to increase weaning weights in younger sows (2nd and 3rd parity), 5432±142.7 and 5,074±142.7 in HMB/D and control piglets, respectively (P < 0.09). In conclusion, these results agree with previous university studies demonstrating CaHMB supplementation increased early piglet weights with a tendency to improve weaning weights.